Novel angiotensin I-converting enzyme inhibitory peptides derived from edible mushroom Agaricus bisporus (J.E. Lange) Imbach identified by LC-MS/MS - Lau, C.C.; Abdullah, N.; Shuib, A.S.; Aminudin, N. (2013)
Angiotensin I-converting enzyme (ACE) inhibitors derived from foods are valuable auxiliaries to agents such as captopril. Eight highly functional ACE inhibitory peptides from the mushroom, Agaricus bisporus, were identified by LC-MS/MS. Among these peptides, the most potent ACE inhibitory activity was exhibited by AHEPVK, RIGLF and PSSNK with IC50 values of 63, 116 and 129μM, respectively. These peptides exhibited high ACE inhibitory activity after gastrointestinal digestion. Lineweaver-Burk plots suggested that AHEPVK and RIGLF act as competitive inhibitors against ACE, whereas PSSNK acts as a non-competitive inhibitor. Mushrooms can be a good component of dietary supplement due to their readily available source and, in addition, they rarely cause food allergy. Compared to ACE inhibitory peptides isolated from other edible mushrooms, AHEPVK, RIGLF and PSSNK have lower IC50 values. Therefore, these peptides may serve as an ideal ingredient in the production of antihypertensive supplements.